P0115 Effect of differential stage or treatment on socioeconomic inequalities in survival from non-small-cell lung carcinoma (NSCLC): Mediation analysis using Osaka population-based cancer registry data in Japan. (July 2015) - Rachet, B.; Ito, Y.; Li, R.; Ioka, A.; Nakayama, T.
Abstract : Background: Wide socioeconomic inequalities in cancer survival were observed in Osaka, Japan. Both 1-year and 5-year survival from non-small-cell lung carcinoma (NSCLC) differed by about 5% between the most affluent and most deprived patients. We aimed to estimate the part played by differential stage distribution and surgical treatment in such inequalities. Methods: We did an observational study using population-based cancer registry data. The final analysis included 30, 528 patients diagnosed with a NSCLC in Osaka Prefecture in 1993–2004, who were followed up for at least 5 years. 11% were excluded because of missing information on tumour stage. Mediation analyses using Monte Carlo simulation were used to estimate the proportion of the socioeconomic effect mediated by tumour stage on (i) cancer survival and (ii) receiving surgical treatment of curative intent. Findings: Compared with the highest socioeconomic patients, higher 1-year mortality in lower socioeconomic groups was mediated by adverse stage distribution in nearly half of cases. Stage explained none of the higher conditional 5-year mortality among lower socioeconomic patients. Lower socioeconomic levels were also associated with decreasing proportions of surgery with curative intent, but this association was mediated by stage only in the lowest socioeconomic group: the lower proportion of treatment was explained by adverse stage distribution in nearly 80% of cases. Interpretation: Access to earlier diagnosis should be deployed in low socioeconomic populations. Suboptimal management observed among the poorest NSCLC patients needs to be further investigated. This is crucial in an equitable society with a universal health-care system.